Mapping Fuel Poverty in Portugal - Simoes, Sofia G. (2018)
The research work underlying this paper was funded by European Economic Area Financial Mechanism EEA - Grants through the project ClimAdaPT. Local, promoted by the APA-Environment Portuguese Agency. The authors acknowledge the work of Tiago Pocas Lopes and of Patricia Fortes that was very valuable to support the estimation of useful energy needs per dwelling.